The Nyanga/Ngororombe Panpipe Dance: 2.Some dance steps for the Nyanga panpipe dance - Tracey, Andrew (International Library of African Music, 1992)
These dance steps were collected during the last week of November 1990 at Moya Aliya Malamusi's home, Singano Village, Chileka, Malawi, from a small group of Nyungwe refugees from Mozambique. The leader of the group of six players was Sakha Blond, whose original home was Goba. They came across from Chifunga refugee camp, Mwanza, near the Malawi-Mozambique border, at Moya's invitation to stay for a few days. We all stayed together in Donald Kachamba's compound while I recorded and worked with them. I am grateful to both Moya and Donald for their hospitality.
Keywords: African Music